Jatibarang Final Solid Waste Dumping Site of Semarang City and Its Problems - Sutarto Edhisono (Diponegoro University, 2015)
Solid waste is big problem in most cities in Indonesia. The problem which often raises, is the difficulty to find the land for solid waste dumping site. The local inhabitants could not accept if the dumping site location is closed to their residential. Therefore, the existing final dumping site is pushed to accommodate and receive solid waste from the entire of the city, although really the service time of the facility is over.This situation is occured on the Jatibarang Final Solid Waste Dumping Site (TPA Jatibarang) of Semarang City, recently.The Municipal of Semarang City, has no other choice for final dumping site exept extending the service time of the TPA Jatibarang. Beside this, the TPA Jatibarang has specific situation, because its location is closed to the Kreo River, one of the tributaries of Garang River, which at the down stream of this river is located intake of the city water supply treatment plant.The leachate of the solid waste is discharged into the Kreo River, which treated by using ordinary aeration method. Of course, this situation is the disadvantage of the TPA Jatibarang. This paper describes the condition of TPA Jatibarang, and its problems and how the efforts of the Municipal of Semarang to overcome this situation.